2013
DOI: 10.1093/trstmh/trt091
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of antigen specific response in individuals with Schistosoma mansoni infection in an endemic area of Minas Gerais, Brazil

Abstract: BackgroundImmunoepidemiologic studies have shown a relationship between IgE and IgG4 antibodies with age and with resistance and susceptibility to infection. It is believed that the IgE and IgG4 responses to soluble egg antigen (SEA) can be used for serological analysis of infection and post-treatment status. This study aimed to evaluate the association between Schistosoma mansoni infection and anti-SEA IgG4 and IgE reactivities, and determine whether these reactivities could be used as biomarkers of infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Interestingly, although the levels of IgG1 raised against RP26 and sm31 declined soon after the PZQ treatment to some extent with significance, IgG1 to serpin significantly declined at 10 weeks after the treatment. The kinetics of the IgG1 response to SEA in this study were similar to those reported by Matoso et al [ 38 ]. Their study was conducted with human sera and suggested that anti-SEA IgG4 reactivity can be used as a biomarker for the serological monitoring of S .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, although the levels of IgG1 raised against RP26 and sm31 declined soon after the PZQ treatment to some extent with significance, IgG1 to serpin significantly declined at 10 weeks after the treatment. The kinetics of the IgG1 response to SEA in this study were similar to those reported by Matoso et al [ 38 ]. Their study was conducted with human sera and suggested that anti-SEA IgG4 reactivity can be used as a biomarker for the serological monitoring of S .…”
Section: Discussionsupporting
confidence: 91%
“…Studies in Brazil evaluating the risks of infection by Matoso et al [ 5 ] showed an increased risk in children and young adults who fished and crossed streams. Similar observations with schoolchildren have been shown by Massara et al [ 35 ], who observed that activities with both high and low water contact exposure (e.g., bathing, fishing, crossing streams, working in agriculture, watering plants and working in sand extraction) were significantly associated with infection.…”
Section: Discussionmentioning
confidence: 99%
“…mansoni infection occurs when individuals enter fecally contaminated water inhabited by infected intermediate hosts ( Biomphalaria glabrata ), the transmission of this neglected tropical disease also has a complex social, biological, and environmental basis that must be considered for successful control and elimination programs. While the importance of these factors in the occurrence of schistosomiasis has been intensively studied [ 3 5 ], the complexity of socioeconomic and behavioral factors can vary considerably on a local level as well as on a global scale. For example, a study conducted on the shores and islands of Lake Victoria in Nyanza Province, Kenya showed that human population density was a major factor driving Schistosoma transmission, with individual socioeconomic factors appearing not to significantly affect transmission [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fraction antigen ELISA (FA-ELISA) is another modified ELISA method, which uses fractionated SEA and provides a high sensitivity and specificity in case detection, as well as providing effective assessment of the efficacy of therapy for S. japonicum infection (139). It has also been shown that IgG4 reactivity to SEA in ELISA can be used as an immune biomarker for the monitoring of infection with S. mansoni in areas of endemicity (140). Recently, the S. mansoni 200-kDa tegumental protein (Sm200) was used in an ELISA for the diagnosis of S. mansoni infection in a murine model, exhibiting more than 90% sensitivity and specificity, denoting it as a promising reagent for diagnosis (141).…”
Section: Antibody Detectionmentioning
confidence: 99%